EXCHANGE RATE FLUCTUATIONS AND THEIR IMPACT ON THE IRAQ`STRADE BALANCE: AN ECONOMETRIC ANALYTICAL STUDY FOR THE PERIOD 2010-2024 - Mustafa Ibrahim Abdullah (Universitas Negeri Malang, 2026)
The influence of the Iraqi economy is closely related with the amount of oil revenue that can be generated by the Iraqi economy, as the oil revenues are one of the important factors that have affected the economic picture of Iraq. In this regard, the study was aimed to study the following: 1- Econometric analysis method of studying the differences between the rates of the currencies and their impact on the trade balance of Iraq during the period (2010-2024). The research has significance as it attempts to explain the impact of exchange rate fluctuations on exports and imports and the overall activity of international trade in a small and undiversified economy, typical of a rentier economy. From the empirical results, it could be inferred that there is a negative relationship between trade balance (Y) and exchange rate (X). The estimated value of the coefficient shows that a 1% increase in the exchange rate leads to an increase in trade balance by 0.8754. This is because it is very dependent upon oil revenues and extremely sensitive to exchange rate fluctuations that can cause very volatile trade balance. The results have also indicated that the non-oil productive sectors have been contributing little share to the foreign trade trade of Iraq and that the oil products trade is still the main contributor to foreign trade trade in Iraq. In addition, the depreciation of the Iraqi dinar has contributed only slightly to the boost in non-oil exports, and has exerted downward pressure on price soared imports of goods and services and contributed to inflationary pressures. Furthermore, the world's oil price fluctuations have a larger effect on Iraq's trade balance than the fluctuations in the exchange rate. It therefore suggests that the economic policies adopted should focus on diversifying and expanding the productive base of the economy; support the industrial and agricultural sectors; promote non-oil exports, and minimize reliance on oil earnings. These would improve the trade stance of Iraq.